UNIT USAHA KESEHATAN SEKOLAH (UKS) SEBAGAI STRATEGI MEMBANGUN GENERASI ISLAMI YANG SEHAT DAN BEBAS STUNTING - Ridha Mardiyani; Lidia Hastuti; Amelyadi; Uji Kawuryan; Hidayah; Imran; Fathul Khair (Institut Kesehatan Yarsi Mataram, 2026)
Background: Adolescents present a highly strategic target group for early stunting interventions through schools and the School Health Unit (UKS), which can facilitate health education, provide service facilities, and reinforce Islamic character. However, many schools lack adequate UKS facilities, which must be addressed to optimize stunting prevention and improve adolescent health. Objective of the Intervention: The intervention aims to enhance knowledge, skills, and spiritual identity by using a UKS approach that integrates health education and UKS training with Islamic and Muhammadiyah values. Methods:The methods employed include a talk show “Islamic Adolescents Prevent Stunting” and UKS cadre training for students and teachers. Results:The intervention led to an average increase in knowledge of 39.4%, with the proportion of students demonstrating good knowledge rising from 47.4% to 86.8%, and students acquiring practical skills such as measuring body weight and height, providing first aid during accidents, and administering basic treatments. The integration of an Islamic dimension strengthened internal motivation and character development among students. Conclusion: The UKS effectively transforms knowledge into healthy lifestyle practices and holds significant potential for long-term stunting reduction.